Grading system of acnes vulgaris - Tran, Thi Quynh Trang; Mai, Ba Hoang Anh (Tạp chí Y Dược Huế, 2024)
Background: Acne vulgaris is an inflammatory disease of the pilosebaceous unit, consisting of comedones, papules, pustules, nodules, and cysts. With the complexity of polymorphic nature, acne vulgaris is inherently difficult to assess and the measurement and grading of this condition is a recognized challenge for clinicians. This article presents a comprehensive preview of acne severity assessment according to timelines to give an overview of methods used to measure acne severity. Methods: A systematic search of the literature was performed to identify publications describing acne classification methods. Many combinations of search terms were used with the help of search engines consisting of Pubmed, Google Scholar, Uptodate, and Medscape. Results: 31 documents were retrieved, of which seven articles were removed because the full-text copy could not be found. After reviewing the content of 24 documents, 12 were excluded as they did not focus on acne outcome instruments, did not present a novel approach, did not focus on assessment of physical symptoms, or were not reported in the English language. Finally, 12 methods were included in the review. Conclusion: Acne vulgaris is a common disease, the diversity of classification is useful and allows clinicians to choose a variety of assessment and investigation methods.